The Effect of Gibberellic Acid (GA3) On The In Vitro Seed Germination of Manggosteen (Garcinia mangostana) - Andini, Andini; Dzaroini, Riska Aqidatud; Resmisari, Ruri Siti (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
Mangosteen is considered as fruit of many benefits with great popularity, rendering it valuable as an export commodity. Unfortunately, it has a relatively slow growth and long early fruiting time. Generative propagation of mangosteen by seed result in low-yielding productionof qualified seedswith recalcitrant nature which means it cannot be stored for a long time. Whereas the result of vegetative propagation using grafting, branch cuttings and budding has difficulty rooting out. Tissue culture method requires growth regulators to control organogenesis and morphogenesis so it can accelerate the growth of the mangosteen explants. This study was arrangedintwo- factor completely randomized design (CRD). The observed variables werethe strength of the medium (½ and 1 MS) and GA3 concentrations (0 ppm; 0.25 ppm; 0.5 ppm; 0.75 ppm and 1 ppm). The variatonson GA3 concentration (0 ppm; 0.25 ppm; 0.5 ppm; 0.75 ppm; 1 ppm) on different strength MS medium (½ MS and 1 MS) did not significantly affect the growth of radicle and sooth in the in vitro seeds germination of Mangosteen (Garcinia mangostana).